Pelatihan Keluarga dalam Penanganan Awal Syok Anafilaktik di Komunitas Berisiko Alergi - Utami, Dia Rejeki; Anurogo, Dito; K, Fitriani. (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Anaphylactic shock is a medical emergency resulting from a severe systemic allergic reaction and can be fatal if not treated quickly and appropriately. In communities with a high history of allergies, family members' limited knowledge and skills in providing initial treatment are risk factors for increased fatalities in anaphylaxis cases. This community service activity aims to increase families' capacity to detect early signs of anaphylactic shock and provide first aid quickly and accurately before medical assistance arrives. The implementation method used an educational and practical approach, including interactive lectures, simulations of the use of epinephrine autoinjectors, and the distribution of written educational modules. Evaluation of training outcomes was conducted through pre- and post-tests, as well as direct observation during the simulation. Results showed significant improvements in family knowledge, skills, and preparedness in handling anaphylaxis incidents. The conclusion of this activity is that family-based training can improve community preparedness in reducing the risk of death from anaphylactic shock. It is recommended that similar training be implemented on an ongoing basis in high-risk areas.